The Relationship Between Financial Ratios and Rate of ReturnRatio on Common Stock Investments in the Capital and Securities Business Sector on the Stock Exchange of Thailand - Supasatitkun, Natamon; Banchenvijit, Wanrapee (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2024)
The objective of this research study was to investigate the relationship between financial ratios and rate of return ratio on common stock investments in the capital and securities business sector on the Stock Exchange of Thailand. The study collected secondary data and analyzed financial ratios from annual financial statements from years 2018 to 2022. Quantitative research methods were employed, including descriptive and inferential statistics, as well as multiple regression analysis, to analyze the data. The results of the research revealed that the panel data relationship analysis using Pool OLS at a significance level (p-value<0.05) found that none of the financial ratios were related to the rate of return ratio. Furthermore, the F-test statistics for the Pool PLS analysis indicated that the F-test value was less than its critical value, leading to the acceptance of the null-hypothesis, which stated that none of the financial ratios were related to the rate of return ratio.